An assessment on crystallization phenomena of Si in Al/a-Si thin films via thermal annealing and ion irradiation. Issue 8 (27th January 2020) - Maity, G.; Dubey, S.; El-Azab, Anter; Singhal, R.; Ojha, S.; Kulriya, P. K.; Dhar, S.; Som, T.; Kanjilal, D.; Patel, Shiv P.
Abstract : In the present study, crystallization of amorphous-Si (a-Si) in Al/a-Si bilayer thin films under thermal annealing and ion irradiation has been investigated for future solar energy materials applications. Abstract : In the present study, crystallization of amorphous-Si (a-Si) in Al/a-Si bilayer thin films under thermal annealing and ion irradiation has been investigated for future solar energy materials applications. In particular, the effect of thickness ratio ( e.g. in Al : a-Si, the ratio of the Al and a-Si layer thickness) and temperature during irradiation on crystallization of the Si films has been explored for the first time. Two sets of samples with thickness ratio 1 : 1 (set-A: 50 nm Al/50 nm a-Si) and thickness ratio 1 : 3 (set-B: 50 nm Al/150 nm a-Si) have been prepared on thermally oxidized Si-substrates. In one experiment, thermal annealing of the as-prepared sample (of both the sets) has been done at different temperatures of 100 °C, 200 °C, 300 °C, 400 °C, and 500 °C. Significant crystallization was found to initiate at 200 °C with the help of thermal annealing, which increased further by increasing the temperature. In another experiment, ion irradiation on both sets of samples has been carried out at 100 °C and 200 °C using 100 MeV Ni 7+ ions with fluences of 1 × 10 12 ions per cm 2, 5 × 10 12 ions per cm 2, 1 × 10 13 ions per cm 2, and 5 × 10 13 ions per cm 2 . Significant crystallization of Si was observed at a remarkably low temperature of 100 °C under ion irradiation. The samples irradiated at 100 °C show better crystallization than the samples irradiated at 200 °C. The maximum crystallization of a-Si has been observed at a fluence of 1 × 10 12 ions per cm 2, which was found to decrease with increasing ion fluence at both temperatures ( i.e. 100 °C & 200 °C). The crystallization of a-Si is found to be better for set-B samples as compared to set-A samples at all the fluences and irradiation temperatures. The present work is aimed at developing the understanding of the crystallization process, which may have significant advantages for designing crystalline layers at lower temperature using appropriate masks for irradiation at the desired location. The detailed mechanisms behind all the above observations are discussed in this paper.